Dissecting common and divergent molecular pathways elicited by CdSe/ZnS quantum dots in freshwater and marine sentinel invertebrates. Issue 2 (7th February 2017) - Ambrosone, Alfredo; Roopin, Modi; Pelaz, Beatriz; Abdelmonem, Abuelmagd M.; Ackermann, Lisa-Maria; Mattera, Lucia; Allocca, Mariateresa; Tino, Angela; Klapper, Markus; Parak, Wolfgang J.; Levy, Oren; Tortiglione, Claudia
Abstract: Water ecosystems represent main targets of unintentional contamination of nanomaterials, due to industrial waste or other anthropogenic activities. Nanoparticle insult to living organisms may occur in a sequential way, first by chemical interactions of the material with the target membrane, then by progressive internalisation and interaction with cellular structures and organelles. These events trigger a signal transduction, through which cells modulate molecular pathway in order to respond and survive to the external elicitation. Therefore, the analysis of the global changes of the molecular machinery, possibly induced in an organism upon exposure to a given nanomaterial, may provide unique clues for proper and exhaustive risk assessment. Here, we tested the impact of core/shell CdSe/ZnS QDs coated by a positively charged polymer on two aquatic species, the polyp Hydra vulgaris and the coral S. pistillata, representative of freshwater and sea habitats, respectively. By using reliable approaches based on animal behaviour and physiology together with a whole transcriptomic profiling, we determined several toxicity endpoints. Despite the difference in the efficiency of uptake, both species were severely affected by QD treatment, resulting in dramatic morphological damages and tissue bleaching. Global transcriptional changes were also detected in both organisms, but presenting different temporal dynamics, suggesting both common and divergent functional responses in the two sentinel organisms. Due to the striking conservation of structure and genomic organisation among animals throughout evolution, our expression profiling offers new clues to identify novel molecular markers and pathways for comparative transcriptomics of nanotoxicity.